EMISI GAS FORMALDEHIDA PAPAN PARTIKEL DARI BEBERAPA JENIS KAYU - Rozak Memed (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The result of determination of formaldehyde emission from particleboard samples glued with urea formaldehyde and mixture of UF and MF resin is reported in this paper. The particleboard samples were selected from two different factories in addition to those prepared in the laboratory at the center.The values of formaldehyde emission of particleboard prepared in the laboratory are between 6.154 ppm (Jeungjing) and 18.720 ppm (meranti kuning), from factory A between 0.295 ppm-7.710 ppm; while from factory B between 13.246 ppm-23.691 ppm. Board samples from factory A glued with mixture of UF and MF resins. on the other hand, show an average emission value of 0.295 ppm.